Chapter 1 - Maize - Otegui, María Elena; Cirilo, Alfredo Gabriel; Uhart, Sergio Adolfo; Andrade, Fernando Hector (Academic Press, 2021)
Maize is presently the grain crop that covers the largest cultivated area, has the largest production, and the largest grain yield worldwide. In recent years, maize occupied an important part of the land previously cropped to other species and moved forward into many newly cultivated areas considered fragile on a global scale. In all cases, it produced extraordinary economic benefits together with serious sustainability concerns. Considering this context and future climate scenarios, in this chapter, we revisit and upgrade the ecophysiological and agronomic concepts that helped maize conquer its current leading status among all cultivated species.